2023
DOI: 10.1371/journal.pone.0285417
|View full text |Cite
|
Sign up to set email alerts
|

Large genomic deletions delineate Mycobacterium tuberculosis L4 sublineages in South American countries

Abstract: Mycobacterium tuberculosis (Mtb) is still one of the primary pathogens of humans causing tuberculosis (TB) disease. Mtb embraces nine well-defined phylogenetic lineages with biological and geographical disparities. The lineage L4 is the most globally widespread of all lineages and was introduced to America with European colonization. Taking advantage of many genome projects available in public repositories, we undertake an evolutionary and comparative genomic analysis of 522 L4 Latin American Mtb genomes. Init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…We showed that MTBC has a compact accessory genome that is acquired verTcally. This finding is consistent with recent research, which found a small accessory genome with a clonal geneTc structure in MTBC (Baena et al, 2023, Ceres et al, 2022, Silva-Pereira et al, 2024. Using a BLASTn analysis approach, we idenTfied core genes that were designated as accessory and further reduced the accessory genome from 613 to 506.…”
Section: Mtbc Accessory Genome Is Small and Is Acquired Ver9callysupporting
confidence: 93%
See 1 more Smart Citation
“…We showed that MTBC has a compact accessory genome that is acquired verTcally. This finding is consistent with recent research, which found a small accessory genome with a clonal geneTc structure in MTBC (Baena et al, 2023, Ceres et al, 2022, Silva-Pereira et al, 2024. Using a BLASTn analysis approach, we idenTfied core genes that were designated as accessory and further reduced the accessory genome from 613 to 506.…”
Section: Mtbc Accessory Genome Is Small and Is Acquired Ver9callysupporting
confidence: 93%
“…It comprises both the core genome, which consists of genes shared by all members of the species, and the accessory genome, which includes genes present in some but not all members (Brockhurst et al, 2019). Previous research has focused on pangenomic invesTgaTons of parTcular MTBC lineages (Baena et al, 2023, Ceres et al, 2022. A recent study invesTgated the MTBC pangenome focusing on protein-coding sequences (Silva-Pereira et al, 2024).…”
Section: Introduc=onmentioning
confidence: 99%
“…The number of genes per genome is also reduced in Clade II, aligning with the observed differences in genome sizes. However, the average protein length remains nearly the same in both clades, suggesting that genome reduction in Clade II may be associated with gene losses, possibly through genome deletions observed in other bacteria (Hershberg et al, 2007;Koskiniemi et al, 2012;Bobay and Ochman, 2017;Baena et al, 2023). Given that many genomes in Clade II are metagenomeassembled genomes (MAGs), future confirmatory analyses are crucial to mitigate potential effects of incomplete genomes on statistical analyses.…”
Section: Discussionmentioning
confidence: 99%
“…The Mtb genomes were sequenced by Novogene (Sacramento, CA, USA) using the Illumina Novaseq 6000 platform, analyzed, and deposited in the NCBI SRA database under the bioproject PRJNA867148 [43].…”
Section: Whole-genome Sequencing and Analysismentioning
confidence: 99%